Pengujian Empiris Pengaruh Ketidakpastian Kebijakan Ekonomi Amerika Serikat Terhadap Dinamika Perekonomian Indonesia - Suwito Suwito; Siswoyo Hari Santosa; Duwi Yunitasari (UPT Penerbitan Universitas Jember, 2020)
The global economic uncertainy situation is one of the phenomena that occurs at this time. Erratic economic policies in developed countries have an impact on the economy in developing countries. This study analyzes the influence of uncertainty in US economic policy on the dynamics of the Indonesian economy. Estimates using the Ordinary Least square method are used to determine the relationship between variables. Then the data used in this study began in 1998Q1-2016Q4. The estimation results show that the dynamics of uncertainty in US economic policies have a significant effect on the Indonesian economy. EPU variables, US exchange rates, and have a significant effect on Indonesia's economic growth. This result is proven by the IRF which indicates the response from the EPU fluctuation which was responded to by the GDP variable in Indonesia. These conditions indicate that the uncertainty of the economic policies of the United States affects the performance of the Indonesian economy.